Classification And Preparation Of Non-Ferrous Scrap Metals And Alloys - H. F. Seifert (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
THE classification and preparation of non-ferrous scrap metals is a subject of interest to every individual and corporation that employs in its processes of manufacture non-ferrous metals and alloys and accumulates in such manufacture scrap from these materials for disposition in the form .of turnings, borings, short ends, punchings, clippings, grindings, washings, etc. All too frequently the disposition-of such scrap is left to individuals who have no knowledge of the subject either from a metallurgical or a commercial standpoint, or both. Much money is thus lost which with a little more intelligent effort might be saved, and in this day of fierce competition and small profits such an opportunity cannot be ignored. The Mineral Resources of the United States for the year 1925, the latest issue available (Part 1, page 221), gives the secondary non-ferrous TABLE 1.-Some. Secondary Non-ferrous Metals Recovered in the United States for the -Year 1924-25 Material Short Tons Value Copper, including that in alloys other than brass.... 250,600 8 71,170,400 Brass, scrap remelted : 242,300 56,270,800 Lead as metal : 112,420 39,477,100 Lead as alloys 112,460 Zinc as metal 61,430 11,359,000 Zinc in alloys other than brass 13,300 Tin as metal 7,950 Tin in alloys 23,000, 35,165,400 Antimony as metal 1 3,794,000 Antimony in alloys : 10,839 Aluminum as metal 17,700 24,816,000 Aluminum in alloys 26,300 Nickel as metal 191 1,518,000 Nickel in non-ferrous alloys 2,109 Total l 882,600 $243,570,700